Mupusti Alam sebagai Etika Lingkungan: Kearifan Ekologis Masyarakat Padepokan Girijaya, Sukabumi - Ahmad Gunawan Sany; Rizky Yazid; Banun Binaningrum (Paradigma: Jurnal Kalam dan Filsafat, 2026)
The environmental crisis stems not only from the exploitation of nature but also from a worldview that treats nature merely as an instrument for satisfying human interests. This article examines mupusti alam as the foundation of environmental ethics among the Girijaya Padepokan community in Sukabumi and its implementation through pamali, rituals, and natural-resource practices. This qualitative field study draws on observation, interviews, and documentation, analyzed descriptively and interpretively through environmental ethics and ecological wisdom. The findings demonstrate that mupusti alam regards nature as part of God’s creation, possessing spiritual value and deserving respect. This worldview is translated into pamali as a mechanism of moral guidance and social control and embodied in forest protection, regulated tree felling, crop rotation, respect for agricultural produce, and the Seren Taun ritual. Nevertheless, waste burning reveals a gap between ecological values and inadequate infrastructure. The study concludes that Girijaya’s environmental ethics constitutes a relational ethic connecting spirituality, customary obedience, and environmental conservation.